1980
DOI: 10.1002/chin.198024180
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: METHYLATION OF 3‐NITRO‐1,2,4‐TRIAZOL‐5‐ONE

Abstract: Methylierungen der Titelverbindung (I) mit Dimethylsulfat/NaOH liefern bei Einsatz von 1 Äquivalent Methylierungsreagenz ‐ Gemische der Monomethylderivate (II)‐(IV), bei Einsatz von 2 Äquivalenten Me2SO4/NaOH entstehen überwiegend die Dimethylderivate (V) und (VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Therefore, if different species are present in the pH 5-9 range, testing should be conducted at 2-3 pH values throughout the pH 5-9 range. NTO is an ionizable compound ( Figure 19) with a pKa of 3.67 (Kofman et al 1980). A pH of 1 ppm NTO solution in deionized water equals to a pH of 4.98.…”
Section: Phototransformation Of Nto and Dnan In Solutionmentioning
confidence: 99%
“…Therefore, if different species are present in the pH 5-9 range, testing should be conducted at 2-3 pH values throughout the pH 5-9 range. NTO is an ionizable compound ( Figure 19) with a pKa of 3.67 (Kofman et al 1980). A pH of 1 ppm NTO solution in deionized water equals to a pH of 4.98.…”
Section: Phototransformation Of Nto and Dnan In Solutionmentioning
confidence: 99%
“…One of the most important IMCs is 3-nitro-1,2,4-triazol-5-one (NTO), which is used in the ammunition formulations IMX-101 and IMX-104. NTO has a high water solubility (16 642 mg/L at 25 °C) and is anionic at circumneutral pH (p K a = 3.76). , As a result, NTO is minimally sorbed, highly mobile, and has a great potential to contaminate soil and groundwater at/near military training ranges and munitions manufacturing sites. Improper waste disposal, spills, and incomplete detonation are some of the sources of IMC contamination in the United States and elsewhere. ,, Controlled detonations of IMX-104 mortar rounds showed that up to 1.2 (in high-order detonations) and 50% (in blow-in-place detonations) of the NTO initially present remained as residues on soils .…”
Section: Introductionmentioning
confidence: 99%
“…NTO has a high water solubility (16 642 mg/L at 25 °C) 1 and is anionic 2 at circumneutral pH (pK a = 3.76). 3,4 As a result, NTO is minimally sorbed, 5 highly mobile, and has a great potential to contaminate soil and groundwater at/near military training ranges and munitions manufacturing sites. Improper waste disposal, spills, and incomplete detonation are some of the sources of IMC contamination in the United States and elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Under the action of equimolar amounts of dimethyl sulfate and alkali, 4-methyl-3-nitro-1,2,4-triazol-5-one is preferentially formed. With a 4-fold molar excess of alkali, the major product is 1-methyl-3-nitro-1,2,4-triazol-5-one, whereas with a 1 : 2 dimethyl sulfate-to-alkali ratio, 5-methoxy-3-nitro-1,2,4-triazole [2,3]. The appreciable formation of the O-methylation product is also observed in dimethylformamide.…”
mentioning
confidence: 71%